DEVELOPMENT OF HIJANIS STYLE APPLICATION USING 3-DIMENSIONAL (3D) MODEL - Raihana Md Saidi; Anis Afiqah Abd Aziz (Journal of Islamic, Social, Economics and Development, 2023)
Hijab Style is becoming more popular as more teenagers and content creators advocate new hijab styles every time, they make a video and upload it online. The traditional hijab style remains popular among Malaysian women; yet, with the advancement of modern technologies and the internet, hijab styles are becoming increasingly diverse. Many mobile applications on the Google Play store assist users in learning the style. However, the majority of them have certain limitations, such as simply exhibiting the model in a two-dimensional image, and some of the applications do offer elements that allow the user to learn the style directly. Furthermore, women take longer than males to get dressed for an outing, and they do not have time to properly pick and style their hijab. Furthermore, women who are new to hijab style will be unsure about what hijab is appropriate for them and how to wear it. It is critical to develop a new platform that helps the user while also being easier to use. This project's objective is to develop a Hijanis-style application utilizing web scraping and a 3-dimensional (3D) model. The viewer may see a 3-dimensional representation of the hijab style and face type (3D). To assist novice hijabsters in learning a new style, a YouTube video instruction will be provided, allowing the user to simply understand and follow the training. The Hijanis Style application will have a 3D model viewer, allowing users to interact with the 3D model and gain a better knowledge of the hijab style.